ENFORCEMENT PROCEDURE ON UNREGISTERED REAL ESTATE OWNERSHIP RIGHT - Stojana, (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2024)
The failure of the judgement debtor to register his right of ownership on real estate is not an obstacle to the determination of execution in the laws of the entities of Bosnia and Herzegovina. In addition, due to the conditioning оf performing the enforcement actions by the registration of the judgement debtor's right to immovable property, the current procedural rules cannot be considered as an adequate normative response of the domestic legislators to the need of the judgement creditor to settle, especially when the judgement debtor has no other assets for settlement. The paper, using scientific methodology, discusses and evaluates the axiological value of legislative solutions to the issue of enforcement against real estate that is not registered as the property of the judgement debtor in domestic law, as well as in the laws of selected neighboring countries. The analysis covers both situations, when the registration of the rights has a constitutive effect, as well as when it has a declarative effect on acquisition of rights of judgement debtor. It is concluded that the temporal correlation between the moment of determination of enforcement against unregistered immovable property and the moment of registration of the judgement debtor as its owner determines at least two possible legislative models of determination of enforcement. Each of the observed models, in which the judgement creditor's forced settlement is conditioned by the previous registration of the judgement debtor as owner of real estate, can be improved, either by solving the problem of efficiently obtaining the basis for the registration of the judgement debtor's right, or by enabling the implementation of the confiscation inventory in a situation where it turns out as impossible for the judgement creditor the acquisition of the judgement debtor's title, and thus the registration of his ownership.
Keywords: registration of real estate; determination of enforcement; confiscation inventory of real estate